2020
DOI: 10.1111/jade.12317
|View full text |Cite
|
Sign up to set email alerts
|

The Shock of the New

Abstract: Since 2017 I have examined the impact of shifting professional practices demonstrated by students of an Artist Teacher MA programme at an English university. Students repeatedly discuss the transformative nature of the course, and through an impact case study I have interrogated the conditions which enable profound changes to occur. Emerging findings indicate that pedagogies of uncertainty enacted within an inclusive community foster students' experiences of visibility, being heard and valued professionally. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Falk & Dierking’s description of how museums connect to ‘the larger lives and realities of individuals, groups and communities’ resonates even more powerfully with me in the light of our experiences designing remote learning resources over the last eighteen months. I sympathise with artist teacher Rachel Payne’s reflections and how lockdown initially felt like ‘a new beginning forced on my world’, but like her I have come to an understanding that the process has been more of ‘a continual becoming of self and community’ (Payne 2020, 736–7) Museums are about people and we found that this vital personal context could be supported and sustained remotely while museums were closed. These experiences are not unique – museum professionals across the globe have been developing this work in the most innovative and inspiring ways.…”
Section: Discussionmentioning
confidence: 82%
“…Falk & Dierking’s description of how museums connect to ‘the larger lives and realities of individuals, groups and communities’ resonates even more powerfully with me in the light of our experiences designing remote learning resources over the last eighteen months. I sympathise with artist teacher Rachel Payne’s reflections and how lockdown initially felt like ‘a new beginning forced on my world’, but like her I have come to an understanding that the process has been more of ‘a continual becoming of self and community’ (Payne 2020, 736–7) Museums are about people and we found that this vital personal context could be supported and sustained remotely while museums were closed. These experiences are not unique – museum professionals across the globe have been developing this work in the most innovative and inspiring ways.…”
Section: Discussionmentioning
confidence: 82%
“…Dewey argued that education is itself a living and should connect students with a democratic society where they can participate in social change and innovation [45]. In progressive education, as well as in arts education, the focus is placed on learning by doing, encouraging participants to explore and discover concepts through hands-on activities and projects [46]. How these essential features can be present when training future teachers in Higher Education Institutions by distance or blended modes of delivery is a crucial question that needs to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers need to inquire into each, to deduce how individual cognitive exchange occurs. Such action would help raise cognitive research contributions in art education, whilst assisting subject protection from neoliberal regime (Payne, 2020). Mukhametzyanova (2021) identified that attitudinal and emotional exchanges co-exist with the cognitive in intercultural and interdisciplinary interactions.…”
Section: Literature Review Strategymentioning
confidence: 99%
“…This has enabled pedagogic transformation and student experience emphasis. Thus, understanding cognitive exchange capacities and their influence in higher education becomes advantageous to educational stakeholders because all parties can develop knowledge of social and political issues beyond subject boundaries (Payne, 2020).…”
Section: Policy and Societymentioning
confidence: 99%